Insect opsin protein sequence alignment - Holland, P; Feuda, R; Marletaz, F; Bentley, M (University of Oxford, 2015)
Sequence alignment described in "Conservation, duplication and divergence of five opsin genes in insect evolution" by Roberto Feuda, Ferdinand Marletaz, Michael Bentley and Peter W H Holland